2018
DOI: 10.1007/s12028-017-0489-1
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Impact of Status Epilepticus Secondary to Intracerebral Hemorrhage: Results from the US Nationwide Inpatient Sample

Abstract: SE is a significant, likely underdiagnosed, predictor of morbidity and mortality after ICH. Future studies are necessary to better identify which patients are at highest risk of SE to guide resource utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…There is uncertainty about the prognostic significance of abnormal electrographic patterns in the setting of ICH. 325,326 The clinical context should therefore be considered in the decision-making process. The recommendation is to initiate antiepileptic medication in the context of an electrographic seizure that is clinically suspected to be contributing to the impaired consciousness in order to improve morbidity (defined as LOS >14 days or discharge to somewhere other than home or a rehabilitation facility).…”
Section: Synopsismentioning
confidence: 99%
See 1 more Smart Citation
“…There is uncertainty about the prognostic significance of abnormal electrographic patterns in the setting of ICH. 325,326 The clinical context should therefore be considered in the decision-making process. The recommendation is to initiate antiepileptic medication in the context of an electrographic seizure that is clinically suspected to be contributing to the impaired consciousness in order to improve morbidity (defined as LOS >14 days or discharge to somewhere other than home or a rehabilitation facility).…”
Section: Synopsismentioning
confidence: 99%
“…One of the primary challenges in this area is that the studies differ on the definition of seizure and method of detection. 325,329,330 Another consideration is that seizures may be a marker of ICH rather than specifically affecting outcomes. 327 Recommendation-Specific Supportive Text 1.…”
Section: Synopsismentioning
confidence: 99%
“…Cerebral injury also accounts for the 62% mortality rate we found in patients exhibiting any type of seizure postoperatively and replicates findings by other researchers who showed that poor outcomes were primarily seen in seizure patients who concomitantly presented with new brain injury [ 3 , 8 , 18 ]. Even if there is no visible structural damage detected in the CCT images, subtle neuronal insults may occur in the context of CPB [ 21 , 22 , 23 ], which cause encephalopathy and might also induce epileptic activity in susceptible patients [ 24 , 25 ]. Especially when cerebral damage has already manifested itself, it becomes even more important to detect NCSE early, so that it can be treated quickly and vigorously in order to prevent additional neuronal injuries, thereby reducing severe disability [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that status epilepticus was an independent risk factor for fatality of the patients with spontaneous cerebral hemorrhage[ 29 ], especially, in the patients with refractory and nonconvulsive epilepsy. These patients often require intubation and mechanical ventilation because these patients might stop breathing and heart-beating.…”
Section: Discussionmentioning
confidence: 99%